Facial nerve schwannomas: management and facial function results - Pablo Casas; Luis Lassaletta; Maria Jose Sarriá; John Gavilán (Turkish Archives of Otorhinolaryngology, 2007)

(untitled)
Objectives: To evaluate the clinical features, diagnosis, treatment options, surgical approaches, and postoperative functional results of facial nerve schwannomas.Methods: The charts of patients affected by facial nerve (FN) schwannomas that were surgically treated at La Paz Hospital between 1992 and 2003 were retrospectively analyzed. Eight cases were included in the study. For all of the patients, the following variables were recorded: age at surgery, sex, initial symptoms, evolution of the facial palsy, lenght of facial palsy, preoperative and postoperative hearing levels, extent of the tumor, surgical approach, facial nerve repair technique, eye closure achievement and length of the follow-up. Preoperative and postoperative FN function was graded according to the House-Brackmann scale.Results: All patients had some degree of facial dysfunction at the time of surgery, facial palsy being the first symptom in 4 patients. Seven patients were affected by conductive or sensorineural hearing loss before surgery. Five patients presented with tinnitus, three with instability, three with pain, and one with othorrea. Lesions were located along the entire length of the nerve. A correct preoperative diagnosis of facial schwannoma was made in 4 cases. The FN was involved by the tumor and had to be interrupted and reconstructed in all the cases. All patients showed a postoperative facial grade III or IV.Conclusion: FN schwannomas should be considered in the differential diagnosis of facial nerve paralysis. However the possibility of normal facial motor function may be considered. As different therapeutic options may be adopted, the management must be individualized, and implication of the patient in the final decision is recommended.